Cavernous Hemangioma of the Scrotum - Nabi, Nosheen; Tahir, Saadia; Tanwani, Ashok Kumar; Khalid, Ahmareen (International Journal of Pathology, 2018)
Scrotal hemangiomas are rare benign neoplasms of the scrotum. Its diagnosis is often missed on ultrasonography. As the incidence of malignant neoplasm of testis is more than the benign neoplasms so radical orchidectomy is usually performed as a management because of suspicion of malignancy and the diagnosis is finally made on the histopathological examination. Reporting these cases emphasise in keeping it in the differentials of testicular neoplasms so that testis are preserved by not performing the orhidectomy thus preventing hypogonadism and infertility.